A glutathione-dependent control of the indole butyric acid pathway supports Arabidopsis root system adaptation to phosphate deprivation. (20th April 2020) - Trujillo-Hernandez, José A; Bariat, Laetitia; Enders, Tara A; Strader, Lucia C; Reichheld, Jean-Philippe; Belin, Christophe
Abstract : Arabidopsis root responses to indole butyric acid (IBA), but not IAA, depend on glutathione levels, and endogenous IBA and glutathione are both required for root system adaptation to phosphate starvation. Abstract: Root system architecture results from a highly plastic developmental process to adapt to environmental conditions. In particular, the development of lateral roots and root hair growth are constantly optimized to the rhizosphere properties, including biotic and abiotic constraints. The development of the root system is tightly controlled by auxin, the driving morphogenic hormone in plants. Glutathione, a major thiol redox regulator, is also critical for root development but its interplay with auxin is scarcely understood. Previous work showed that glutathione deficiency does not alter root responses to indole acetic acid (IAA), the main active auxin in plants. Because indole butyric acid (IBA), another endogenous auxinic compound, is an important source of IAA for the control of root development, we investigated the crosstalk between glutathione and IBA during root development. We show that glutathione deficiency alters lateral roots and root hair responses to exogenous IBA but not IAA. Detailed genetic analyses suggest that glutathione regulates IBA homeostasis or conversion to IAA in the root cap. Finally, we show that both glutathione and IBA are required to trigger the root hair response to phosphate deprivation, suggesting an important role for this glutathione-dependent regulation of the auxin pathway in plant developmental adaptation to its environment.